2013
DOI: 10.1093/brain/awt054
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals mutated SLC19A3 in patients with an early-infantile, lethal encephalopathy

Abstract: To accomplish a diagnosis in patients with a rare unclassified disorder is difficult. In this study, we used magnetic resonance imaging pattern recognition analysis to identify patients with the same novel heritable disorder. Whole-exome sequencing was performed to discover the mutated gene. We identified seven patients sharing a previously undescribed magnetic resonance imaging pattern, characterized by initial swelling with T2 hyperintensity of the basal nuclei, thalami, cerebral white matter and cortex, pon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 26 publications
(34 reference statements)
11
100
0
Order By: Relevance
“…In 2013, the research team of van den Knaap identified a distinct MRI pattern [6] in seven patients with lethal leukoencephalopathy (out of more than 3000 MRIs). Using WES technology they linked this condition to SLC19A3 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2013, the research team of van den Knaap identified a distinct MRI pattern [6] in seven patients with lethal leukoencephalopathy (out of more than 3000 MRIs). Using WES technology they linked this condition to SLC19A3 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Using WES technology they linked this condition to SLC19A3 mutations. The pattern includ- MRIs, atrophy of affected structures" [6]. Acute, postacute, intermediate and end stage of the disease were specified in that study [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations